Preparation of chromium complexes for ethylene tetramerization catalyst - Park, Jun Hyeong; Park, Ju Yong; Baek, Jun Won; Seo, Yeong Hyun; Lee, Mi Ryu; Lee, Junseong; Lee, Bun Yeoul (Bulletin of the Korean Chemical Society, 2024)
One of the remaining challenges in the commercialization of a highly efficient ethylene tetramerization catalyst, [1-CrCl2][B(C6F5)4] (1=iPrN[P(C6H4Si(Octyl)3)2]2), is the generation of small amounts of polyethylene (PE). To address this issue, we explored different activator options and found that (Octyl)3Al was the most effective choice. Building on the observation that [iPrN(PPh2)2]CrCl3(THF) was not completely alkylated by the action of excess Me3Al to form ([iPrN(PPh2)2]Cr(μ2-Cl)(ClMe2AlClAlMe3))2, we synthesized [ortho-(MeO)C6H4CH2-η1C:κO]3Cr, developing a catalytic system comprising this precursor, PNP ligand 1, and [MeN(H)(C18H37)2][B(C6F5)4]. However, this catalytic system exhibited a long induction time (~30 min) and generated a significant amount of PE. Returning to the catalytic system of [1-CrCl2][B(C6F5)4], we successfully achieved the conversion of [(EtOH)4CrCl2][B(C6F5)4] to [(CH3CN)4CrCl2][B(C6F5)4] at a large scale by designing a specialized glass apparatus. Finally, we discovered that the generation of PE could be reduced by adjusting the reaction conditions during the synthesis of [1-CrCl2][B(C6F5)4].
Keywords: 1-octene; 1-octene production; Bis(phosphine) ligand; Catalytic system; Chromium catalysts; Ethylene tetramerization; Phosphine ligands; Tetrakis; Tetrakis(pentafluorophenyl)borate; Tetramerization; 1-octene production; bis(phosphine) ligand; chromium catalyst; ethylene tetramerization; tetrakis(pentafluorophenyl)borate